IMPLEMENTASI KOMBINASI ALGORITMA GOST PADA KEAMANAN DATA TEXT DAN KOMPRESI DATA MENGGUNAKAN ALGORITMA DMC - Devi Afnita; Efori Buulolo; Noferianto Sitompul (STMIK Budi Darma, 2018)
Cryptography comes from the word crypto which means secret and graphy which means writing. So cryptography can be interpreted as a secret writing. The term can be defined as the study of mathematical techniques related to information security. To send information quickly with a large enough file size, it will certainly take a long time. This delivery speed depends on the size of the information sent. One solution to overcome this problem is by placing (compression) data before sending using a compression algorithm with the principle to reduce the size of the file, so that when the delivery process can be done quickly. The purpose of this study was to combine Government Standard (Gost) encryption algorithms and Dynamic Markov Compression (DMC) compression algorithms.Keywords: Cryptography, Government Standard (Gost), Dynamic Markov Compression (DMC).